Analysis of wind turbine blade deformation with STFT method - (:unkn) unknown (SILA SCIENCE, 2012)
This study is intended for investigating electrical and mechanical faults of electro-mechanical systems in wind turbine. In the study, generator rotor speed, generator torque and gear torque occurred as a result of possible blade fault at wind turbine are investigated. This fault is analyzed by creating model and Short Time Fourier Transform (STFT) that is one of signal processing techniques is used. Blade faulty condition is compared with healthy condition. Obtained results are quite consistent and it proven to be used as a method of determining fault.
Keywords: Wind turbines; Blade fault analysis; STFT; Condition monitoring; FAULT-DIAGNOSIS; SPEED; INTERVAL; MOTORS